Case Report: Rowell Syndrome–Like Flare of Cutaneous Lupus Erythematosus Following COVID-19 Infection - Drenovska, Kossara; Shahid, Martin; Mateeva, Valeria; Vassileva, Snejina (Frontiers in Medicine, 2022)
The current COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had an important impact on dermatology practice, posing diagnostic and therapeutic challenges especially in patients with inflammatory and autoimmune skin disorders. Disease-specific and nonspecific cutaneous manifestations have been increasingly reported in the spectrum of COVID-19 but the influence of the infection on pre-existing dermatologic diseases has not been clearly defined. There has been a debate in the literature as to whether patients suffering from autoimmune dermatoses, including cutaneous lupus erythematosus (CLE), are at increased risk of SARS-CoV-2 infection, as well as if they experience worsening of their LE-related clinical symptoms. The present article reports on a case of Rowell syndrome occurring after COVID-19 in a 67-year old woman with pre-existing chronic CLE manifesting with few discoid lesions on the face, scalp and upper chest, successfully controlled with topical corticosteroids and photoprotection. Erythema multiforme (EM)-like eruption developed approximately two weeks after the SARS-CoV-2 infection, the latter being confirmed by positive nasopharyngeal swab and successfully treated with systemic antibiotics and antiaggregants. Diffuse hair loss and patches of cicatricial alopecia were also present upon scalp examination. Laboratory work-up, including routine tests, histologic, immunofluorescent and serologic investigations, was supportive to the diagnosis. Administration of topical and systemic corticosteroids along with peroral hydroxychloroquine resulted in progressive improvement of the cutaneous lesions. Rowell syndrome is a rare entity in the spectrum of LE, characterized by EM-like lesions, photosensitivity, and positive antinuclear and anti-Ro antibodies, that is currently considered to be a variant of subacute CLE (SCLE). Several cases of SCLE have been described in association with medications, including anti-SARS-CoV-2 vaccines but only a few reports incriminate the infection itself as a potential exacerbating factor. Based on the clinical course of the disease, we suggest that the observed Rowell syndrome-like flare of CLE was related to the COVID-19 infection in this patient.